Synergistic Effects of Toll-Like Receptor 1/2 and Toll-Like Receptor 3 Signaling Triggering Interleukin 27 Gene Expression in Chikungunya Virus-Infected Macrophages - Valdés-López, Juan Felipe; Fernandez, Geysson J.; Urcuqui-Inchima, Silvio (Frontiers in Cell and Developmental Biology, 2022)
Chikungunya virus (CHIKV) is the etiological agent of chikungunya fever (CHIKF), a self-limiting disease characterized by myalgia and severe acute or chronic arthralgia. CHIKF is associated with immunopathology and high levels of pro-inflammatory factors. CHIKV is known to have a wide range of tropism in human cell types, including keratinocytes, fibroblasts, endothelial cells, monocytes, and macrophages. Previously, we reported that CHIKV-infected monocytes-derived macrophages (MDMs) express high levels of interleukin 27 (IL27), a heterodimeric cytokine consisting of IL27p28 and EBI3 subunits, that triggers JAK-STAT signaling and promotes pro-inflammatory and antiviral response, in interferon (IFN)-independent manner. Based on the transcriptomic analysis, we now report that induction of IL27-dependent pro-inflammatory and antiviral response in CHIKV-infected MDMs relies on two signaling pathways: an early signal dependent on recognition of CHIKV-PAMPs by TLR1/2-MyD88 to activate NF-κB-complex that induces the expression of EBI3 mRNA; and second signaling dependent on the recognition of intermediates of CHIKV replication (such as dsRNA) by TLR3-TRIF, to activate IRF1 and the induction of IL27p28 mRNA expression. Both signaling pathways were required to produce a functional IL27 protein involved in the induction of ISGs, including antiviral proteins, cytokines, CC- and CXC- chemokines in an IFN-independent manner in MDMs. Furthermore, we reported that activation of TLR4 by LPS, both in human MDMs and murine BMDM, results in the induction of both subunits of IL27 that trigger strong IL27-dependent pro-inflammatory and antiviral response independent of IFNs signaling. Our findings are a significant contribution to the understanding of molecular and cellular mechanisms of CHIKV infection.